Eukaryotic translation initiation factor 4E family member nCBP facilitates the accumulation of TGB-encoding viruses by recognizing the viral coat protein in potato and tobacco - Chen, Ruhao; Yang, Manhua; Tu, Zhen; Xie, Fangru; Chen, Jiaru; Luo, Tao; Hu, Xinxi; Nie, Bihua; He, Changzheng (Frontiers in Plant Science, 2022)
Due to their limited coding capacity, plant viruses have to depend on various host factors for successful infection of the host. Loss of function of these host factors will result in recessively inherited resistance, and therefore, these host factors are also described as susceptibility genes or recessive resistance genes. Most of the identified recessive resistance genes are members of the eukaryotic translation initiation factors 4E family (eIF4E) and its isoforms. Recently, an eIF4E-type gene, novel cap-binding protein (nCBP), was reported to be associated with the infection of several viruses encoding triple gene block proteins (TGBps) in Arabidopsis. Here, we, for the first time, report that the knockdown of nCBP in potato (StnCBP) compromises the accumulation of potato virus S (PVS) but not that of potato virus M (PVM) and potato virus X (PVX), which are three potato viruses encoding TGBps. Further assays demonstrated that StnCBP interacts with the coat proteins (CPs) of PVS and PVM but not with that of PVX, and substitution of PVS CP in the PVS infectious clone by PVM CP recovered the virus infection in StnCBP-silenced transgenic plants, suggesting that the recognition of PVS CP is crucial for StnCBP-mediated recessive resistance to PVS. Moreover, the knockdown of nCBP in Nicotiana benthamiana (NbnCBP) by virus-induced gene silencing suppressed PVX accumulation but not PVM, while NbnCBP interacted with the CPs of both PVX and PVM. Our results indicate that the nCBP orthologues in potato and tobacco have conserved function as in Arabidopsis in terms of recessive resistance against TGB-encoding viruses, and the interaction between nCBP and the CP of TGB-encoding virus is necessary but not sufficient to determine the function of nCBP as a susceptibility gene.